Comparison Of Hyomental Distance Ratio And Neck Circumference To Thyromental Distance Ratio For Predicting Difficult Visualisation Of Larynx In Intensive Care Unit, An Observational Study (The Review of Diabetic Studies, 2025)
Background: Anticipating Difficult Visualization of Larynx (DVL) allows the practitioner to be prepared in order to prevent failure of intubation. This study was done to compare the usefulness of Hyomental Distance Ratio (HMDR) versus Neck Circumference to Thyromental Distance Ratio (NC/TMD) in predicting DVL in Diabetic  ICU patients.Methods: 115 ICU patients with   diabetes mellitus of age  18-60 years, of both genders, undergoing tracheal intubation were included in study. Using steel ruler, distance from tip of hyoid bone to anterior part of mentum was measured with head in neutral position (HMDn). Distance was then measured with head extended (HMDe). HMDR was calculated. Neck circumference was measured at the level of thyroid cartilage. Thyromental distance was measured from thyroid notch to mentum in full head extension. NC/TMD ratio was calculated. Patients were preoxygenated, induced and paralysed. Glottis was visualised using direct laryngoscopy, by an experienced anaesthesiologist and graded according to Modified Cormack Lehane’s grading.Results: Average age of the subjects included in the study was around 45.07±12.48 years. Incidence of difficult laryngoscopy in our study was found to be 18.26%. As per statistical analysis using Chi-square test, results showed strong significance. Sensitivity of HMDR was 90.48% and specificity was 91.49% with a cut-off of ≥1.2. Sensitivity of NC/TMD ratio was found to be 85.71% and specificity was 87.17% with a cut-off of ≤5. The overall accuracy was also higher with HMDR over NC/TMD ratio. Thus, HMDR was an easy and reliable indicator of DVL compared to NC/TMD.Conclusion: Hyomental Distance Ratio is a better predictor of Difficult Visualisation of Larynx compared to Neck Circumference to Thyromental Distance Ratio in Diabetic  ICU patients. A combination of tests yields better accuracy.Categories: Anaesthesiology, Critical Care